O ensino de história no liceu paraibano oitocentista (1839-1886) - Morais, Maday de Souza (2016)
Our work is a possible example of writing and dialogue about the field of School Subjects and Teaching of History. Through the sources worked by (the) researchers (as) of Paraiba History of Education of the nineteenth century - official documents (reports, speeches, speeches, messages and offices of provincial presidents and directors of Public Instruction), dictionaries, laws and regulations, maps, database, newspapers and historiographical framework, we were uniting information and building knowledge of knowledge, science, chair and history of discipline in Paraiba secondary education - we seek also infer the debate, influence and the limits of discipline History in the school of the nineteenth century Paraíba, as well as concerns about the "quality of education", both with regard to the teacher / student relationship, the association with other knowledge, as the domain of the material used. Another feature of our work was to emphasize the communication between subjects that make up the secondary public education in Paraíba of the nineteenth century - teachers, students, directors of public education, the provincial presidents, inspectors, community - both inside and outside the walls of secondary school. We emphasize also that the figures were extremely important for the evaluation of the number of students - enrollment and attendance - chairs, materials, among others; as well as their relationship with the reports / legislation allowed more consistent interpretations of the configuration of the construction of school knowledge for the teaching of history. Thus, based on the assumptions and possibilities raised by cultural history, we make an approach focusing on school culture and school material culture - works, objects and methods - with emphasis on studies of School Subjects and Teaching of History.